2023
DOI: 10.1590/1519-6984.247701
|View full text |Cite
|
Sign up to set email alerts
|

Enterotoxigenic methicillin resistant Staphylococcus aureus contamination in salted fish from Gwadar Balochistan

Abstract: Staphylococcus aureus is an important foodborne pathogen associated to food intoxication and other multiple infections in human being. Its presence in salted food is a serious issue due to its salt tolerance potential. A study was conducted to analyze the presence of enterotoxins producing drug resistance S. aureus in salted sea fish from Gwadar. Freshly persevered samples (n=50) of salted fish were subjected to analyze the presence of S. aureus using 16S rRNA and Nuc genes primers. The isolates were then eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…We detected nine enterotoxin genes in all of our farmed fish isolates. Staphylococcal enterotoxins have also been detected in other studies of S. aureus in fish and fishery products ( 34 , 57 ). Staphylococcal food poisoning is caused by the ingestion of any of the 27 characterized staphylococcal enterotoxins ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 67%
“…We detected nine enterotoxin genes in all of our farmed fish isolates. Staphylococcal enterotoxins have also been detected in other studies of S. aureus in fish and fishery products ( 34 , 57 ). Staphylococcal food poisoning is caused by the ingestion of any of the 27 characterized staphylococcal enterotoxins ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 67%
“…We detected nine enterotoxin genes in all our farmed fish isolates. Staphylococcal enterotoxins have also been detected in other studies of S. aureus in fish and fishery products (71,72). Staphylococcal food poisoning is caused by the ingestion of any of the 27 characterised Staphylococci enterotoxins (27,28).…”
Section: Discussionmentioning
confidence: 93%
“…Staphylococcus aureus , a well-known foodborne pathogen, can be found even under adverse environmental conditions. Foods that are rich in protein and carbohydrates are highly likely to be contaminated by S. aureus , which causes food poisoning [ 63 ]. The results of the present study showed that none of the experimental groups (FM and SSDM) had Staphylococcus aureus , as shown in Table 5 .…”
Section: Resultsmentioning
confidence: 99%